All‐Carbon Hybrid Mobile Ion Capacitors Enabled by 3D Laser‐Scribed Graphene. Issue 6 (24th March 2020) - Zhang, Fan; Zhang, Wenli; Guo, Jing; Lei, Yongjiu; Dar, Mushtaq A.; Almutairi, Zeyad; Alshareef, Husam N.
Abstract : Hybrid mobile ion capacitors (HMIC) are proposed as a way to incorporate the advantages of both batteries and supercapacitors into one system. Unfortunately, considering the much slower Li + intercalation/deintercalation process, finding a suitable battery anode material with a high rate performance is still a major challenge. Herein, the fabrication of nitrogen‐doped laser‐scribed graphene (NLSG) with a 3D structure as a binder‐free and conductive additive‐free anode is reported. This NLSG anode has high nitrogen and oxygen doping (8.6 and 6.3 at%), leading to the formation of conductive electrodes with an expanded lattice spacing, providing more convenient pathways and reaction sites for Li + ions. Hybrid Li‐ion capacitors (HLICs) are assembled by combining the NLSG anodes with hierarchical porous carbon (PC) cathodes. The NLSG//PC HLICs show an energy density (including the total weight of two electrodes) of 186 Wh kg −1 at 200 W kg −1 . Even when power density increases to the level of conventional supercapacitors (20 kW kg −1 ), an energy density of 76 Wh kg −1 is still be obtained. Further, the devices exhibit excellent cycle life, retaining 87.5% of the initial value after 5000 cycles. Herein, laser‐scribed graphene is demonstrated as a very promising electrode for mobile ion capacitors. Abstract : Laser‐scribed nitrogen‐doped 3D graphene (NLSG) is demonstrated as a binder‐free, conductive, and additive‐free anode for hybrid Li‐ion capacitors (HLICs). The hybrid capacitors are assembled by combining 3D graphene anodes with porous carbon (PC) cathodes. The NLSG//PC HLICs show an energy density (including the total weight of two electrodes) of 186 Wh kg −1 at 200 W kg −1 .